2008
DOI: 10.1074/jbc.m706987200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cullin-box Sequences That Direct Recruitment of Cul2-Rbx1 and Cul5-Rbx2 Modules to Elongin BC-based Ubiquitin Ligases

Abstract: The Elongin BC-box protein family includes the von Hippel-Lindau tumor suppressor and suppressor of cytokine signaling proteins, which are substrate recognition subunits of structurally related classes of E3 ubiquitin ligases composed of Elongin C-Elongin B-Cullin 2-Rbx1 (Cul2 ubiquitin ligases) or of Elongin C-Elongin B-Cullin 5-Rbx2 (Cul5 ubiquitin ligases). The Elongin BC complex acts as an adaptor that links a substrate recognition subunit to heterodimers of either Cullin 2 (Cul2) and RING finger protein R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
165
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(177 citation statements)
references
References 32 publications
9
165
3
Order By: Relevance
“…Multiple sequence alignment of LRR-1 with selected BC/Cul-2 boxcontaining proteins from C. elegans revealed that these two motifs are conserved in LRR-1. In particular, the key residues that mediate binding to ELC-1 and CUL-2 (Stebbins et al, 1999;Vasudevan et al, 2007;Mahrour et al, 2008) are invariant in LRR-1 (Fig. 1B), suggesting that it is a bona fide substrate-recruitment subunit of a CRL2 complex in C. elegans.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple sequence alignment of LRR-1 with selected BC/Cul-2 boxcontaining proteins from C. elegans revealed that these two motifs are conserved in LRR-1. In particular, the key residues that mediate binding to ELC-1 and CUL-2 (Stebbins et al, 1999;Vasudevan et al, 2007;Mahrour et al, 2008) are invariant in LRR-1 (Fig. 1B), suggesting that it is a bona fide substrate-recruitment subunit of a CRL2 complex in C. elegans.…”
Section: Resultsmentioning
confidence: 99%
“…1A). The BC/Cul-2 box includes two short sequences, termed BC and the Cul-2 box, that are required for ELC-1 and CUL-2 binding, respectively (Vasudevan et al, 2007;Mahrour et al, 2008). Through proteomic screens in mammalian cells (HEK293T), we and others have identified LRR-1 as a potential substrate-recognition subunit of a CRL2 complex (Kamura et al, 2004;Olma et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…2G; supplementary material Table S4). Therefore, among the 16 BC-box proteins that were recently identified in FLAG-ElonginB pulldowns (Mahrour et al, 2008), only Lrrc14, Lrr1 and Fem1 stably associated with the CSN. Similarly, only four BTB proteins (Btbd1, Btbd2, Klhldc5 and Klhl18) were systematically identified in the CSN immunoprecipitates (Fig.…”
Section: The Proteomic Interaction Network Of the Mammalian Cop9 Signmentioning
confidence: 99%
“…Cellular proteins bind to Cul2-based ligase complexes through a VHL box and to Cul5 complexes through a SOCS box. Both are comprised of an Elongin B and C binding domain (BC box) followed by a Cul2 or Cul5 binding domain, with an average 10 to 25 amino acids separating the two (7,9). In some viral proteins, however, these domains can also be quite distant, as is the case for the LANA protein, where they are over 800 amino acids apart (26).…”
Section: Resultsmentioning
confidence: 99%
“…While the BC box domains have been identified in the early region 4 open reading frame 6 (E4 34K, or E4orf6) protein of human adenovirus type 5 (Ad5), the location of the Cullin domains has remained elusive (3,8). The Cullin binding domain within other viral proteins has been located in most of the examples listed in Table 1, only about half of which follow the cellular consensus sequence (LPxP for Cul5, and LxxxLxxxL for Cul2) (7,9). Thus, it seems equally likely that human adenoviruses might utilize either a cellular consensus domain or a novel sequence to bind Cullin 2 or 5.…”
mentioning
confidence: 99%